The Role of Google Classroom in ELT - Sukmawati, Sukmawati; Nensia, Nensia (Universitas Malikussaleh, 2019)
Google Classroom is to offer a platform of blended learning in schools in order to simplify creating assignments and getting the grade out to the students in a paperless way. There are many facilities provided by Google classroom, they are: it will make easier for teachers to carry out learning activities, the intended learning is not only in class, but also outside the classroom because students can learn wherever and whenever by accessing google classroom online. Subject that relating to discuss as in the mobile that emphasize the acquisition of observational skills; and allow students to see the concept of teaching and learning material. The main purpose of the study is to investigate a role of Google classroom in English Language Teaching (ELT). The data was collected through an interview with 16 respondents. This study helped the decision makers of the higher educational institutions to have a better understanding of the role of using Google classroom by their students. It is assumed that it helped in measuring the level of students’ attention to the previously mentioned technology.